The higher-order structure of early maladaptive schemas: A meta-analytical approach - Thimm, Jens C. (Frontiers in Psychiatry, 2022)
Early maladaptive schemas (EMSs) are themes regarding oneself and one’s relationship with others. In schema therapy, 18 EMSs are described that were initially proposed to be clustered in five domains. The current EMS model comprises four domains. However, empirical investigations into the grouping of EMSs have yielded divergent results. The purpose of the present study was to use a meta-analytical approach to examine the higher-order organization of EMSs. To be included in the statistical analyses, studies had to report the associations between all 18 EMSs using a form of the Young Schema Questionnaire. In a systematic literature review in PsycInfo, Embase, MEDLINE, Web of Science, and Google scholar, 27 studies were identified that reported the associations between EMSs in 33 independent samples (N = 13,958, Mage = 16 to 72.3 years, 64.0% female). The correlations between EMSs were pooled across samples and analyzed using confirmatory factor analysis (CFA) and principal component analysis (PCA). The CFA results showed weak support for any of the previously suggested EMS domains. After PCA, four EMS domains were retained that closely resembled the theoretically proposed organization of EMSs. The four components showed fair to good congruence in the clinical and nonclinical subsamples. However, a model with three EMS domains showed a simpler structure. The results suggest a need for further theoretical and empirical clarification of the higher-order structure of EMSs.